Community forest management practices in far-western lowlands of Nepal - Shrestha, B (Banko Janakari, 2009)
Wider discussions are held as to the contribution of community forestry program in Nepal to improve the forest condition and meeting the forest product requirements. This paper presents findings from a study of six Community Forest User Groups in far-western lowlands of Kailali and Kanchanpur in Nepal. The groups with natural and plantation forests have varied experiences in forest conservation and distribution of products. Some groups are resourceful in terms of availability of forest products from the natural forests. Others with plantation forests are product scarce from their own and depend on government managed forest and other sources to meet their demands. The role of concerned government authorities and federation of groups would be instrumental to analyse demand and supply, and make provisions for distribution of forest products within and outside groups and district. Key words: Community forest management, forest products, distribution, far-western low land doi: 10.3126/banko.v18i2.2170 Banko Janakari, Vol. 18, No. 2, 25-34